Assessment of the Depth of the Deformed Layer in the Roller Burnishing Process - Kowalik, M.; Mazur, T.; Trzepiecinski, T. (Проблемы прочности, 2018)
This paper presents the methods used to determine the depth of the plastically deformed top layer in the roller burnishing process. An analytical method was developed for determining the depth of the plastically deformed layer on the basis of the Hertz–Bielayev theory. The depth of deformation was obtained as a function of the process parameters: burnishing force, material strength and roller radius. The analytical solution has been verified using an original method based on the measurement of the face profile of rings. A mathematical model for a theoretical solution and a plan for experimental tests have been developed. The numerical simulation of the depth of the plastically deformed layer was carried out based on the finite element method. The results of deformation depth as a function of roller force, material strength and roller geometry show a good agreement between analytical and experimental methods. Наведено методики визначення глибини пластично деформованого верхнього шару матеріалу при обкочуванні роликом. Аналітичний метод розроблено на основі теорії Герца Беляєва. Глибину такого шару отримано як функцію зусилля обкочування, міцності матеріалу і геометрії ролика. Аналітичний розв'язок перевірено оригінальним методом, що базується на вимірюванні лицьового профілю кілець. Розроблено математичну модель теоретичного розв'зку і план експериментів. Чисельне моделювання глибини пластично деформованого шару виконано методом скінченних елементів. Результати, отримані аналітичним і експериментальним методами, показують їх хорошу відповідність. Представлены методики определения глубины пластично деформированного верхнего слоя материала в процессе обкатывания роликом. Аналитический метод разработан на основе теории Герца Беляева. Глубина такого слоя получена как функция усилия обкатывания, прочности материала и геометрии ролика. Аналитическое решение проверено оригинальным методом, основанным на измерении лицевого профиля колец. Разработаны математическая модель теоретического решения и план экспериментов. Численное моделирование глубины пластично деформированного слоя выполнено методом конечных элементов. Результаты, полученные аналитическим и экспериментальным методами, показывают их хорошее соответствие.